2019
DOI: 10.15809/irriga.2019v24n1p86-97
|View full text |Cite
|
Sign up to set email alerts
|

Crescimento, Produção E Consumo Hídrico Do Quiabeiro Submetido À Salinidade Em Condições Hidropônicas

Abstract: CRESCIMENTO, PRODUÇÃO E CONSUMO HÍDRICO DO QUIABEIRO SUBMETIDO À SALINIDADE EM CONDIÇÕES HIDROPÔNICAS     FRANCISCO JOSÉ NUNES MODESTO1; MARIA ÂNGELA CRUZ MACÊDO DOS SANTOS1; TALES MILER SOARES2 E ELLEN PAULA MENEZES DOS SANTOS3   1 Engenheiro Agrônomo, Mestre em Engenharia Agrícola, Universidade Federal do Recôncavo da Bahia, Núcleo de Engenharia de Água e Solo, Rua Rui Barbosa, S/N, Cruz das Almas-BA, CEP 44.380-000, e-mail: fjmodesto@gmail.com; angela_macedo.08@hotmail.com … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 13 publications
1
8
1
Order By: Relevance
“…Several authors reported a decrease in dry masses of leaves and stem in okra plants grown under saline stress (Ünlükara et al, 2008;Nascimento et al, 2017;Modesto et al, 2019). The differences related to the results obtained in this study comparing with the ones found in literature can be explained, partly, due to the genetic variability and to growing conditions, as in protected cultivation the plants show a lower water requirement.…”
Section: Developmentcontrasting
confidence: 52%
See 2 more Smart Citations
“…Several authors reported a decrease in dry masses of leaves and stem in okra plants grown under saline stress (Ünlükara et al, 2008;Nascimento et al, 2017;Modesto et al, 2019). The differences related to the results obtained in this study comparing with the ones found in literature can be explained, partly, due to the genetic variability and to growing conditions, as in protected cultivation the plants show a lower water requirement.…”
Section: Developmentcontrasting
confidence: 52%
“…The ionic effect causes toxicity in the plant due to a high concentration of specific ions in soil and nutritional imbalance, due to the reduction in the uptake of essential elements for development (Munns & Tester, 2008;Silva et al, 2013;Flowers et al, 2015). All these characteristics can result in a lower water uptake and, consequently, nutrient uptake too, causing a reduction in photosynthesis, growth, yield and fruit quality (Taiz et al, 2017;Modesto et al, 2019).…”
Section: Resumo Suplementação Com Cálcio Nas Soluções Nutritivas Para Mitigar O Estresse Salino No Quiabeiro Fertirrigadomentioning
confidence: 99%
See 1 more Smart Citation
“…These were evident from the symptoms of nutritional deficiency and toxicity and, consequently, premature senescence of the plants and reduced growth. Modesto et al (2019) reported that excess Na + resulted in symptoms that hampered the plant metabolism, such as oxidative stress of proteins, nucleic acids, and lipids and, when combined with toxicity by Cl -, resulted in reduced nutrient assimilation, plant growth, and development, leading to premature senescence. Soares et al (2016) evaluated the effect of six water salinity levels used for the preparation of the nutrient solution (0.2, 1.2, 2.2, 3.2, 4.2, and 5.2 dS m -1 ) and two strategies for replacing the evapotranspirated blade (brackish water from the respective treatment in experiment I) and (supply water [0.2 dS m -1] in experiment II).…”
Section: Resultsmentioning
confidence: 99%
“…The cauliflower tolerance to salt stress was evaluated individually for each cultivar, based on the relative inflorescence fresh matter yield, using the plateau model with linear decrease proposed by Maas and Hoffman (1977). The parameters of the model were adjusted by minimizing the square of errors with the Solver tool of the Microsoft Excel, as done by Modesto et al (2019).…”
Section: Methodsmentioning
confidence: 99%